Etnografi Komunikasi Suku Dayak hindu Budha Bumi Segandu Indramayu (SDHBBSI) - Mira Renata; Taufiq Furqon Nurhakim; Robby Rachman Nurdiantara (KOMVERSAL, 2025)
This study explores the communication ethnography of the Dayak Hindu-Buddhist Bumi Segandu Indramayu (SDHBBSI) community in Krimun Village, Losarang Subdistrict, Indramayu Regency. The background of this research is based on the uniqueness of the SDHBBSI community, which possesses cultural and spiritual identities distinct from those of the surrounding population, despite being geographically and biologically native to Indramayu. The aim of this research is to gain an in-depth understanding of the communication dynamics within the SDHBBSI community. The study employs a communication ethnography method with a qualitative approach, involving participatory observation, in-depth interviews, and document analysis. The findings reveal that the SDHBBSI community maintains its cultural identity through cultural symbols, rituals, and daily communication. Rituals such as Kungkum and Mepe serve as means to strengthen social and spiritual bonds within the community. Despite the challenges posed by modernization, the community has managed to preserve its traditions without compromising its identity.